Esophagogastric Cancers: Integrating Immunotherapy Therapy Into Current Practice. Issue 24 (20th August 2022) - Patel, Monica A.; Kratz, Jeremy D.; Lubner, Sam J.; Loconte, Noelle K.; Uboha, Nataliya V.
Abstract : Immunotherapy (IO) agents have led to significant improvements in patient outcomes across many tumor types. There have been great efforts to introduce immune checkpoint inhibitors into the treatment paradigm of esophagogastric cancers as well. A number of randomized phase III trials, which will be reviewed here, established the role of these agents in both early-stage and advanced-stage disease. Adjuvant nivolumab is US Food and Drug Administration–approved after neoadjuvant chemoradiation and resection of esophageal and gastroesophageal junction cancers on the basis of the phase III CheckMate 577 trial. In the advanced setting, patients with programmed death receptor ligand-1–positive tumors should be recommended IO in combination with chemotherapy in the first-line setting on the basis of the results from KEYNOTE 590, CheckMate 649, and CheckMate 648. Across trials, chemotherapy continues to play a critical role in the first-line setting and should be offered to all patients who are eligible for systemic therapy, including those with biomarker select tumors. In the later lines of treatment, IO has modest activity, and prior studies have grown largely irrelevant because of the enrollment of IO-naive patients. Similar to other disease types, patients with microsatellite unstable (microsatellite instability high) tumors represent a unique cohort that is more sensitive to IO. However, there are no randomized studies evaluating how best to apply IO in early or advanced stages specifically for the treatment of patients with microsatellite instability high upper GI tumors. Questions remain how to best select patients who benefit from IO treatments, how to augment IO activity in programmed death receptor ligand-1–negative tumors, and how to incorporate IO in late-line settings or for recurrent disease that has been treated with IO-containing regimens during early stages.